2014
DOI: 10.3892/mmr.2014.2749
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from breast cancer cells stimulate proliferation and inhibit apoptosis of CD133+ cancer cells in vitro

Abstract: Exosomes are a family of bioactive vesicles that are secreted from various types of cell, including tumor cells. Exosomes derived from breast cancer cells have been demonstrated to perform important functions in tumor progression in vitro and in vivo. However, few studies exist regarding the function of exosomes in CD133+ breast cancer cells. In the present study, exosomes from 4T1 mouse breast cancer cells and mouse mammary gland epithelial cells were purified. The exosome-associated markers CD63, CD9 and CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…For example, exosomes from 4T1 breast cancer cell mouse models were found to increase proliferation and suppress apoptosis of CD133 ϩ 4T1 cells, supporting the potential role of exosomes in tumor progression through evading apoptosis (35 ). Other studies, including human cells/clinical samples supporting a role for exosomes in evading apoptosis, are outlined below.…”
Section: Apoptosismentioning
confidence: 81%
“…For example, exosomes from 4T1 breast cancer cell mouse models were found to increase proliferation and suppress apoptosis of CD133 ϩ 4T1 cells, supporting the potential role of exosomes in tumor progression through evading apoptosis (35 ). Other studies, including human cells/clinical samples supporting a role for exosomes in evading apoptosis, are outlined below.…”
Section: Apoptosismentioning
confidence: 81%
“…MCF-7-derived exosomes up-regulated the activation marker CD44, the CSCs growth factor IL6, as well as ApoE. In another study, 4T1 mouse breast derived exosomes functioned as pro-tumorigenic factors by promoting the cell growth and suppression apoptosis of CD133 + tumor stem cells [75]. …”
Section: Exosomes Contribute To Tumor Progression Via Modulating Stemmentioning
confidence: 99%
“…Extracellular membrane trafficking via exosomes and other plasma membrane-derived vesicles can promote tumor growth and metastasis [50]. Many studies have demonstrated that CD133-containing vesicles are involved in a series of important biological processes such as cell differentiation, cancer progression, and extracellular cell communication [15][16][17]. However, the underlying mechanisms of CD133 secretion remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission electron microscopy and sucrose density gradient fraction analysis showed that in addition to its localization in plasma membrane protrusions, CD133 is also found in EVs [14]. CD133-containing secretory vesicles are involved in biological processes such as cell differentiation [15], cancer progression [16], and extracellular cell communication [17]. Our previous study found that CD133-containing vesicles could be taken up by the recipient cells and promote recipient cells migration [14].…”
mentioning
confidence: 98%